Pregnant women’s profile attended by the family health program in a Ceará’s health region: subsidy to the assistance - Moura, Escolástica Rejane Ferreira; Rodrigues, Maria Socorro Pereira; Silva, Raimunda Magalhães da (Rev Rene, 2005)
The study had as an objective the identification and analysis of 30 profiles of pregnant women who are inhabitants of one of Ceará’s health microregions – Baturité. The data were collected through interviews, in the months of May and June of 2001. It has been found that 13 (43,4%) of the pregnant women were in the extremes of childbearing age; 21 (70%) had not even finished grade school; 4 (13,3%) did not have any source of income and 23 (76,7%) reached an income of up to one hundred reais (R$ 100,00) a month; 7 (23,35%) women had had four or more pregnancies, one of them having her eighth pregnancy and another one having her twelfth pregnancy; 26 (86,7%) had not planned the pregnancy, even so, 22 (73,4%) of them were very satisfied with the pregnancy. The necessity of the FHP’s teams to plan their actions on the basis of the clientele’s profile has been demonstrated, otherwise, a far-reaching impact will not be achieved in the mother’s and in the baby’s health conditions.